Endovascular treatment for basilar artery occlusion: a cost-effectiveness analysis based on a meta-analysis - Wang, Li; Yu, Ying; Zhou, Limei; Xu, Ping; Guo, Xianbin; Xie, Yu; Cai, Junxiu; Pan, Min; Tang, Jie; Gong, Qingtao; Su, Rong; Lou, Yake; et al. (Frontiers in Neurology, 2023)
Objective This study aimed to investigate the efficacy and economic effect of endovascular treatment (EVT) combined with standard medical treatment (SMT) vs. SMT alone in Chinese patients with basilar artery occlusion (BAO) from the perspective of the Chinese healthcare system. Methods We conducted a cost-effectiveness analysis using the results from a meta-analysis comparing EVT and SMT efficacy in Chinese patients with BAO-induced stroke using direct medical costs from the China National Stroke Registry. The meta-analysis’s primary outcome was excellent functional outcome (mRS scores of 0–2), with secondary outcomes being poor functional outcome (mRS scores of 3–5) and death (mRS score of 6). To compare EVT plus SMT’s cost-effectiveness with that of SMT alone, we constructed a combined decision tree and Markov model with a lifetime duration and a 3-month cycle length. The primary cost-effectiveness outcome was the incremental cost-effectiveness ratio (ICER), representing the incremental cost per incremental quality-adjusted life year (QALY). EVT was considered cost-effective if the ICER was lower than the willingness-to-pay (WTP) threshold of three times the per capita gross domestic product (GDP) in 2021 in China; otherwise, it would not be cost-effective. Results The meta-analysis results indicated that EVT could increase the incidence of excellent functional outcomes, with a risk ratio (RR) of 2.23 (95% confidence interval, CI, 1.18–4.21), p = 0.01. Simultaneously, EVT reduced the risk of poor functional outcome and mortality in the EVT group, with RRs of 0.83 (95% CI, 0.67–1.03), p = 0.09, and 0.71 (95% CI, 0.59–0.85), p = 0.0002, respectively. The study also found that EVT plus SMT resulted in a lifetime effectiveness of 2.15 QALY (3.88 life years) for 32,213 international dollars (Intl.$) per patient with BAO. In contrast, SMT alone achieved an effectiveness of 1.46 QALY (3.03 life years) with a total cost of Intl.$ 13,592 per patient. The ICER was Intl.$ 27,265 per QALY (Intl.$ 22,098 per life-year), which fell below the WTP threshold. Conclusion Compared to SMT, EVT improves the prognosis of BAO-induced stroke. Considering the Chinese healthcare system, adding EVT to SMT proves to be cost-effective for patients with BAO compared to SMT alone.